Enzymatic photopolymerization preparation method of fully-reduced polyaniline positive electrode material

Through the enzyme-catalyzed photopolymerization preparation method, the problem of doping ions in the synthesis of all-reduced polyaniline cathode materials in the prior art is solved, and the preparation of materials with high energy density and excellent electrochemical properties is achieved, which improves production efficiency and reduces costs.

CN119505230APending Publication Date: 2025-02-25SHENZHEN JANAENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411592902.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult to synthesize a high energy density fully reduced polyaniline cathode material in one step, and doped ions are introduced during the synthesis, resulting in poor electrochemical performance.

Method used

The enzyme-catalyzed photopolymerization preparation method is adopted to dissolve aniline monomer, surfactant and biomass enzyme in an organic solvent, and perform ultraviolet-induced photopolymerization reaction, followed by solid-liquid separation and nanoification treatment to obtain a fully reduced polyaniline positive electrode material.

Benefits of technology

The preparation of a fully reduced polyaniline cathode material with high product purity, strong reaction controllability and excellent electrochemical performance is achieved, avoiding the introduction of doped ions, improving production efficiency and reducing operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505230A_ABST
    Figure CN119505230A_ABST
Patent Text Reader

Abstract

The invention discloses an enzyme catalytic photopolymerization preparation method of a fully reduced polyaniline positive electrode material. The method comprises the following steps: S1, mixing raw materials: respectively weighing an aniline monomer, a surfactant and a biomass enzyme according to a ratio, and dissolving in an organic solvent to obtain an aniline raw material solution; s2, photopolymerization reaction: carrying out polymerization reaction on the polyaniline raw material solution in S1 under the ultraviolet-induced irradiation condition to obtain a product solution; s3, separation of a first product: carrying out solid-liquid separation on the product solution obtained in the step S2, and drying to obtain the first product; and S4, nanocrystallization treatment: carrying out nanocrystallization treatment on the first product obtained in S3 to obtain the fully reduced polyaniline positive electrode material. The enzyme catalysis photopolymerization preparation method of the fully-reduced polyaniline positive electrode material has the characteristics of high product purity, strong reaction controllability and excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, and in particular to a method for preparing a fully reduced polyaniline positive electrode material by enzyme-catalyzed photopolymerization. Background Art

[0002] Polyaniline materials can be divided into fully oxidized polyaniline, doped polyaniline, intrinsic polyaniline, and fully reduced polyaniline according to the degree of oxidation (consistent with the degree of doping). When polyaniline is used as a positive electrode material, it belongs to a p-type material. At present, the polyaniline purchased and synthesized on the market are all doped polyaniline. Due to the addition of acid and initiator during the synthesis process, it contains some anion doping, resulting in a decrease in the number of active sites, a low theoretical specific capacity, and poor electrochemical performance.

[0003] At present, polyaniline mainly refers to doped polyaniline (ES), but the doped ions (S, Cl, etc.) in ES will increase the proportion of inactive units of polyaniline, reduce the theoretical capacity of polyaniline, and make the electrochemical performance not outstanding enough. The higher the oxidation degree of polyaniline, the lower the specific capacity released.

[0004] Therefore, to obtain polyaniline with high specific capacity, it is necessary to synthesize fully reduced polyaniline. The theoretical capacity of fully reduced polyaniline is 294 mAh g -1 , which has great advantages in p-type materials. However, the existing technology for obtaining fully reduced polyaniline from doped polyaniline requires further processing, which is cumbersome. Summary of the invention

[0005] The purpose of the present invention is to provide an enzyme-catalyzed photopolymerization preparation method for a fully reduced polyaniline cathode material, which has the characteristics of high product purity, strong reaction controllability and excellent electrochemical performance.

[0006] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a fully reduced polyaniline cathode material by enzyme catalysis photopolymerization, comprising the following steps: S1. Raw material mixing: weighing aniline monomer, surfactant and biomass enzyme respectively according to proportion and dissolving them in an organic solvent to obtain a raw material solution of aniline; S2, photopolymerization reaction: subjecting the polyaniline raw material solution of S1 to a polymerization reaction under ultraviolet light initiation irradiation to obtain a product solution; S3, separation of the first product: solid-liquid separation and drying of the product solution obtained in step S2 to obtain the first product; S4, nano-processing: the first product obtained in S3 is subjected to nano-processing to obtain a fully reduced polyaniline positive electrode material.

[0007] In the prior art, fully reduced polyaniline can only be synthesized after removing the doping of doped polyaniline, but fully reduced polyaniline cannot be synthesized in one step. This is mainly because during the synthesis, the acid solution dissolves the aniline, and the initiator chemically initiates the polymerization reaction. These factors make the aniline inevitably doped with anions during the polymerization process. Accordingly, the preparation method of the present invention makes the following improvements to the synthesis process: for example, the synthesis process uses an organic solvent instead of the acid solution to achieve the purpose of completely dissolving the aniline, and at the same time, no doping anions are introduced; for example, light initiation is used instead of chemical initiation of the polymerization reaction, which is environmentally friendly and avoids the introduction of doping ions; for example, biomass enzymes are added to catalyze its photopolymerization, and these enzymes can usually reduce the by-products of the reaction. For example, the polyaniline obtained by chemical synthesis is mainly a micron structure, and the material can be ball-milled and nano-processed to reduce the particle size of the material, shorten the ion diffusion path, and improve the rate performance of the material. The present invention systematically improves the traditional synthesis route, eliminates the introduction of doped ions from the reaction raw materials and the reaction end, and can obtain a fully reduced polyaniline positive electrode material with high energy density in one step. Compared with the traditional water-based reaction system, which can only obtain doped polyaniline and then needs to undergo a reduction step, the production efficiency is doubled and the operating cost is greatly reduced.

[0008] Furthermore, in step S1, the mass ratio of aniline to surfactant is 1-3. The molecules of surfactant can divide the solid particle aggregates into fine particles, disperse them and suspend them in the solution, and play a role in promoting the uniform dispersion of solid particles. Less surfactant makes the dispersion effect poor; too much surfactant will cause the surfactant to be unable to contact the solvent, and then this part of the surfactant will not work at all.

[0009] Furthermore, in step S1, the mass ratio of aniline to biomass enzyme is 1-5. The biomass enzyme plays the role of catalyst and oxidant in the synthesis process. If there is less biomass enzyme, the catalytic effect is not obvious, resulting in a slower polymerization reaction and a low degree of polymerization of the chain segments; if there is more biomass enzyme, the unreacted biomass enzyme will react with the benzene ring, resulting in aniline peroxidation, destruction of the aniline structure, and production of by-products.

[0010] Furthermore, in step S1, the mass ratio of aniline to organic solvent is 3-20. The organic solvent is too small to dissolve the aniline monomer, and a large amount of monomers cannot participate in the photo-initiated polymerization. The solvent is too large and the concentration of the reaction system is low. Photopolymerization is a chain polymerization reaction caused by the activation of aniline into free radicals by light, and the two reactive groups must be at an appropriate distance to react. The concentration is low, resulting in a low probability of collision of aniline monomer molecules, and photo-initiated polymerization is difficult to react.

[0011] Furthermore, in step S2, the ultraviolet light initiation method is ultraviolet light irradiation, and the ultraviolet light wavelength is 250-400nm. Since photopolymerization must absorb wavelengths within a specific range, aniline is excited to an excited state and becomes a free radical to undergo a chain polymerization reaction. Therefore, if the wavelength is too low or too high, the polymerization reaction will not be initiated.

[0012] Furthermore, in step S3, the solid-liquid separation is carried out by filtration and / or centrifugal separation.

[0013] Further, in step S3, the drying method is one or more of freeze drying, vacuum drying, and forced air drying, and the drying time is 5-20 hours. The organic solvent in the material synthesis process must be removed to achieve the purpose of drying the material, and the drying time cannot be too short; since the fully reduced polyaniline contains more -NH-, the thermal stability of -NH- is weak, so a longer drying time will lead to the breakage of the polyaniline chain. In the present invention, for the traditional vacuum oven and forced air drying, the temperature rises rapidly, resulting in the agglomeration of the material. In order to avoid the agglomeration of polyaniline at high temperature, freeze drying is preferred.

[0014] Furthermore, in step S4, the nano-forming method is one or more of mechanical grinding, impact grinding, ball milling, etching, and air flow milling.

[0015] Further, in step S4, in the present invention, the nano-processing method is preferably ball milling, and the control conditions of nano-processing are ball milling speed of 200-400 rpm and time of 3-10 h. During the ball milling process, the collision and friction between the ball milling beads and the particles cause the particles to break and the particle size to decrease. The nano-processing effect is not obvious at a lower speed and a shorter time; however, long-term ball milling is conducive to the refinement of particles, but excessive ball milling may cause excessive refinement of particles and agglomeration, thereby affecting the uniformity of particle distribution.

[0016] Furthermore, the organic agent is one or more of toluene, n-hexane, dichloromethane (DCM), and N-methylpyrrolidone (NMP); the surfactant is one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), polyoxyethylene fatty alcohol ether (F127), fatty acid sorbitan, polyoxyethylene derivative alkylolamide, polyol monofatty acid ester, and essential oil emulsifier; and the biomass enzyme is one or more of horseradish peroxidase (HRP), laccase, and soybean peroxidase.

[0017] The enzyme-catalyzed photopolymerization preparation method of a fully reduced polyaniline cathode material of the present invention has the following beneficial effects: The polymerization reaction is initiated by light instead of chemical initiation, and does not require traditional initiators, which is environmentally friendly and avoids the introduction of doped ions. Enzymes are added during the reaction to obtain polyaniline under milder conditions without pollution. Enzymes are renewable and have high selectivity for aromatic compounds, which can reduce the by-products of the reaction. Compared with chemical polymerization, no initiator is introduced, avoiding the addition of doped ions and salt pollution. Organic solvents are used in the synthesis process instead of acid solutions to achieve the purpose of completely dissolving aniline. At the same time, the salt formed by aniline is avoided as a reactant, and doped anions are not introduced. Fully reduced polyaniline can be directly polymerized. The controllability of the reaction process can be achieved and the purity of the product can be effectively improved.

[0018] At the same time, the polyaniline obtained by chemical synthesis is mainly a micron structure, and the material can be nano-processed to reduce the particle size of the material, shorten the ion diffusion path, and improve the material's rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM image of the fully reduced polyaniline (LB) synthesized in Example 1-4; Figure 2 LB-1 synthesized in Example 1 is applied to sodium ion batteries (a) first week charge and discharge curve, (b) current density of 1 C (1 C = 200 mA g -1 ) Cycle curve; Figure 3 LB-2 synthesized in Example 2 is applied to sodium ion batteries (a) first week charge and discharge curve, (b) current density of 1 C (1 C = 200 mA g -1 ) Cycle curve; Figure 4 LB-3 synthesized in Example 3 is applied to sodium ion batteries (a) first week charge and discharge curve, (b) current density 1C (1 C = 200 mA g -1 ) Cycle curve; Figure 5 LB-4 synthesized in Example 4 is applied to sodium ion batteries, (a) charge and discharge curves in the first week; Figure 6 This is the charge and discharge curve of the sodium ion battery assembled from LB-3 synthesized in Example 3 at low temperature. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0021] The present invention discloses a method for preparing a fully reduced polyaniline cathode material by enzyme catalysis photopolymerization, comprising the following steps: S1. Raw material mixing: weighing aniline monomer, surfactant and biomass enzyme respectively according to proportion and dissolving them in an organic solvent to obtain a raw material solution of aniline; S2, photopolymerization reaction: subjecting the polyaniline raw material solution of S1 to a polymerization reaction under ultraviolet light initiation irradiation to obtain a product solution; S3, separation of the first product: solid-liquid separation and drying of the product solution obtained in step S2 to obtain the first product; S4, nano-processing: the first product obtained in S3 is subjected to nano-processing to obtain a fully reduced polyaniline positive electrode material.

[0022] Furthermore, in step S1, the mass ratio of aniline to surfactant is 1-3.

[0023] Furthermore, in step S1, the mass ratio of aniline to biomass enzyme is 1-5.

[0024] Furthermore, in step S1, the mass ratio of aniline to the organic solvent is 3-20.

[0025] Furthermore, in step S2, the ultraviolet light is induced by irradiating with an ultraviolet lamp, and the wavelength of the ultraviolet light is 250-400nm.

[0026] Furthermore, in step S3, the solid-liquid separation is carried out by filtration and / or centrifugal separation.

[0027] Furthermore, in step S3, the drying method is one or more of freeze drying, vacuum drying, and forced air drying, preferably freeze drying, and the drying time is 5-20 hours.

[0028] Furthermore, in step S4, the nano-forming method is one or more of mechanical grinding, impact, ball milling, etching, and air flow milling, preferably one or more of ball milling.

[0029] Furthermore, in step S4, the control conditions for nano-milling are a ball milling speed of 200-400 rpm and a time of 3-10 h.

[0030] Furthermore, the organic agent is one or more of toluene, n-hexane, dichloromethane (DCM), and N-methylpyrrolidone (NMP); the surfactant is one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), polyoxyethylene fatty alcohol ether (F127), fatty acid sorbitan, polyoxyethylene derivative alkylolamide, polyol monofatty acid ester, and essential oil emulsifier; and the biomass enzyme is one or more of horseradish peroxidase (HRP), laccase, and soybean peroxidase.

[0031] Example 1 Step 1: Weigh 0.1 g of aniline monomer, 0.1 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) surfactant and 0.3 g of horseradish peroxidase (HRP) respectively, and dissolve them in 2 g of dichloromethane (DCM) to obtain a mixed solution of aniline. The whole process is protected from light; Step 2: Pour the polyaniline mixed solution of step 1 into an open culture dish and irradiate the mixture with an ultraviolet lamp at a wavelength of 300 nm; Step 3: freeze-dry the product after centrifugation in step 2 for 5 h to obtain a dry solid substance; Step 4: The dried solid material obtained in the above step 3 was subjected to ball milling nano-processing at a ball milling speed of 200 rpm for 3 h to obtain a solid material LB-1; Step 5: Electrode material preparation. The electrode was prepared by rolling a mixture of 60 wt% of synthesized fully reduced polyaniline (LB-1), 30 wt% of Ketjen black (KB), and 10 wt% of polytetrafluoroethylene (PTFE) into a film with a thickness of about 1 mm. The film was then dried in a vacuum oven at 100 °C overnight and pressed onto an aluminum mesh. The mass of the working electrode was ~2 mg cm -2 ; Step 6: Prepare electrolyte: 1 M NaClO4 / EC-DEC (v / v=1:2) + 1% FEC ester electrolyte.

[0032] Step 7, battery assembly. Using LB-1 as the working electrode, Na as the reference electrode and counter electrode, the above-prepared electrolyte, and a porous polypropylene microporous membrane as a separator, a sodium button cell was assembled in a glove box with a water / oxygen content of less than 1 ppm, and its electrochemical performance was tested by charge and discharge.

[0033] Example 2 Step 1: Weigh 0.3 g of aniline monomer, 0.3 g of P123 polyoxyethylene fatty alcohol ether (F127) and 0.5 g of soybean peroxidase (SBP) respectively, dissolve them in 4 g of dichloromethane (DCM) to obtain a mixed solution of aniline. The whole process is protected from light; Step 2: Pour the polyaniline mixed solution of step 1 into an open culture dish and irradiate the mixture with an ultraviolet lamp at a wavelength of 350 nm; Step 3: freeze-dry the product after centrifugation in step 2 for 8 h to obtain a dry solid substance; Step 4: The dried solid material obtained in the above step 3 was subjected to ball milling nano-processing at a ball milling speed of 300 rpm for 6 h. The obtained solid was recorded as LB-2. Step 5: Electrode material preparation. The electrode was prepared by rolling a mixture of 60 wt% of synthesized fully reduced polyaniline (LB-2), 30 wt% of Ketjen black (KB), and 10 wt% of polytetrafluoroethylene (PTFE) into a film with a thickness of about 1 mm. The film was then dried in a vacuum oven at 100 °C overnight and pressed onto an aluminum mesh. The mass of the working electrode was ~2 mg cm -2 ; Step 6: Prepare electrolyte: 1 M NaClO4 / EC-DEC (v / v=1:2) + 1% FEC ester electrolyte.

[0034] Step 7, battery assembly. Using LB-2 as the working electrode, Na as the reference electrode and counter electrode, the above-prepared electrolyte, and a porous polypropylene microporous membrane as a separator, a sodium button cell was assembled in a glove box with a water / oxygen content of less than 1 ppm, and its electrochemical performance was tested by charge and discharge.

[0035] Example 3 Step 1: Weigh 1.0 g of aniline monomer, 2.0 g of fatty acid sorbitan surfactant and 2.5 g of horseradish peroxidase (HRP) respectively, dissolve them in 3 g of benzene solution to obtain a mixed solution of aniline, and keep it away from light throughout the process; Step 2: Pour the polyaniline mixed solution of step 1 into an open culture dish and irradiate the mixture with an ultraviolet lamp at a wavelength of 350 nm; Step 3: freeze-dry the product after centrifugation in step 2 for 15 h to obtain a dry solid substance; Step 4: The dried solid material obtained in the above step 3 was subjected to ball milling for nano-milling at a ball milling speed of 350 rpm for 9 h to obtain a solid material LB-3; Step 5: Electrode material preparation. The electrode was prepared by rolling a mixture of 60 wt% of synthesized fully reduced polyaniline (LB-3), 30 wt% of Ketjen black (KB), and 10 wt% of polytetrafluoroethylene (PTFE) into a film with a thickness of about 1 mm. The film was then dried in a vacuum oven at 100 °C overnight and pressed onto an aluminum mesh. The mass of the working electrode was ~2 mg cm -2 ; Step 6: Prepare electrolyte: 1 M NaClO4 / EC-DEC (v / v=1:2) + 1% FEC ester electrolyte.

[0036] Step 7, battery assembly. Using LB-3 as the working electrode, Na as the reference electrode and counter electrode, the above-prepared electrolyte, and a porous polypropylene microporous membrane as a separator, a sodium button cell was assembled in a glove box with a water / oxygen content of less than 1 ppm, and its electrochemical performance was tested by charge and discharge.

[0037] Example 4 Step 1: Weigh 2.0 g of aniline monomer, 2.5 g of polyoxyethylene fatty alcohol ether (F127) and 2.5 g of horseradish peroxidase (HRP) respectively, dissolve them in 20 g of toluene solution to obtain a mixed solution of aniline. This process is kept away from light; Step 2: Pour the polyaniline mixed solution of step 1 into an open culture dish and irradiate the mixture with an ultraviolet lamp at a wavelength of 400 nm; Step 3: freeze-dry the product after centrifugation in step 2 for 20 h to obtain a dry solid substance; Step 4: The dried solid material obtained in the above step 3 was subjected to ball milling nano-processing at a ball milling speed of 300 rpm for 9 h, and the obtained solid was recorded as LB-4; Step 5: Electrode material preparation. The electrode was prepared by rolling a mixture of 60 wt% of synthesized fully reduced polyaniline (LB-4), 30 wt% of Ketjen black (KB), and 10 wt% of polytetrafluoroethylene (PTFE) into a film with a thickness of about 1 mm. The film was then dried in a vacuum oven at 100 °C overnight and pressed onto an aluminum mesh. The mass of the working electrode was ~2 mg cm -2 ; Step 6: Prepare electrolyte: 1 M NaClO4 / EC-DEC (v / v=1:2) + 1% FEC ester electrolyte.

[0038] Step 7, battery assembly. Using LB-4 as the working electrode, Na as the reference electrode and counter electrode, the above-prepared electrolyte, and a porous polypropylene microporous membrane as a separator, a sodium button cell was assembled in a glove box with a water / oxygen content of less than 1 ppm, and its electrochemical performance was tested by charge and discharge.

[0039] Example 5 Step 1: Weigh 2.0 g of aniline monomer, 5.0 g of P123 polyoxyethylene fatty alcohol ether (F127) and 6.0 g of soybean peroxidase (SBP) respectively, dissolve them in 15 g of dichloromethane (DCM) to obtain a mixed solution of aniline. The whole process is protected from light; Step 2: Pour the polyaniline mixed solution of step 1 into an open culture dish and irradiate the mixture with an ultraviolet lamp at a wavelength of 400 nm; Step 3: freeze-dry the product after centrifugation in step 2 for 15 h to obtain a dry solid substance; Step 4: The dried solid material obtained in the above step 3 was subjected to ball milling nano-processing at a ball milling speed of 300 rpm for 8 h. The obtained solid was recorded as LB-5. Step 5: Electrode material preparation. The electrode was prepared by rolling a mixture of 60 wt% of synthesized fully reduced polyaniline (LB-5), 30 wt% of Ketjen black (KB), and 10 wt% of polytetrafluoroethylene (PTFE) into a film with a thickness of about 1 mm. The film was then dried in a vacuum oven at 100 °C overnight and pressed onto an aluminum mesh. The mass of the working electrode was ~2 mg cm -2 ; Step 6: Prepare electrolyte: 1 M NaClO4 / EC-DEC (v / v=1:2) + 1% FEC ester electrolyte.

[0040] Step 7, battery assembly. Using LB-5 as the working electrode, Na as the reference electrode and counter electrode, the above-prepared electrolyte, and a porous polypropylene microporous membrane as a separator, a sodium button cell was assembled in a glove box with a water / oxygen content of less than 1 ppm, and its electrochemical performance was tested by charge and discharge.

[0041] Example 6 Step 1: Weigh 1.0 g of aniline monomer, 1.0 g of polyoxyethylene fatty alcohol ether (F127) and 1.0 g of horseradish peroxidase (HRP) respectively, and dissolve them in 3 g of toluene solution to obtain a mixed solution of aniline. The whole process is protected from light; Step 2: Pour the polyaniline mixed solution of step 1 into an open culture dish and irradiate the mixture with an ultraviolet lamp at a wavelength of 250 nm; Step 3: freeze-dry the product after centrifugation in step 2 for 5 h to obtain a dry solid substance; Step 4: The dried solid material obtained in the above step 3 was subjected to ball milling nano-processing at a ball milling speed of 200 rpm for 3 h, and the obtained solid was recorded as LB-6; Step 5: Electrode material preparation. The electrode was prepared by rolling a mixture of 60 wt% of synthesized fully reduced polyaniline (LB-6), 30 wt% of Ketjen black (KB), and 10 wt% of polytetrafluoroethylene (PTFE) into a film with a thickness of about 1 mm. The film was then dried in a vacuum oven at 100 °C overnight and pressed onto an aluminum mesh. The mass of the working electrode was ~2 mg cm -2 ; Step 6: Prepare electrolyte: 1 M NaClO4 / EC-DEC (v / v=1:2) + 1% FEC ester electrolyte.

[0042] Step 7, battery assembly. Using LB-6 as the working electrode, Na as the reference electrode and counter electrode, the above-prepared electrolyte, and a porous polypropylene microporous membrane as a separator, a sodium button cell was assembled in a glove box with a water / oxygen content of less than 1 ppm, and its electrochemical performance was tested by charge and discharge.

[0043] Example 7 Step 1: Weigh 3 g of aniline monomer, 9.0 g of polyoxyethylene fatty alcohol ether (F127) and 15.0 g of horseradish peroxidase (HRP) respectively, dissolve them in 60 g of toluene solution to obtain a mixed solution of aniline. The whole process is protected from light; Step 2: Pour the polyaniline mixed solution of step 1 into an open culture dish and irradiate the mixture with an ultraviolet lamp at a wavelength of 400 nm; Step 3: freeze-dry the product after centrifugation in step 2 for 10 h to obtain a dry solid substance; Step 4: The dried solid material obtained in the above step 3 was subjected to ball milling nano-processing at a ball milling speed of 400 rpm for 10 h. The obtained solid was recorded as LB-7. Step 5: Electrode material preparation. The electrode was prepared by rolling a mixture of 60 wt% of synthesized fully reduced polyaniline (LB-7), 30 wt% of Ketjen black (KB), and 10 wt% of polytetrafluoroethylene (PTFE) into a film with a thickness of about 1 mm. The film was then dried in a vacuum oven at 100 °C overnight and pressed onto an aluminum mesh. The mass of the working electrode was ~2 mg cm -2 ; Step 6: Prepare electrolyte: 1 M NaClO4 / EC-DEC (v / v=1:2) + 1% FEC ester electrolyte.

[0044] Step 7, battery assembly. Using LB-7 as the working electrode, Na as the reference electrode and counter electrode, the above-prepared electrolyte, and a porous polypropylene microporous membrane as a separator, a sodium button cell was assembled in a glove box with a water / oxygen content of less than 1 ppm, and its electrochemical performance was tested by charge and discharge.

[0045] The test results of the above embodiments are as follows Figure 1-6 As shown: Figure 1 The SEM data of the fully reduced polyaniline (LB) synthesized in Examples 1-4. All materials are nanostructured, and the nanoparticles in Example 3 (LB-3) are not agglomerated but rather dispersed; Figure 2 LB-1 synthesized in Example 1 was applied to sodium ion batteries. (a) First week charge and discharge data. The first week charge and discharge capacity was: 135 / 123 mAh g -1 (b)The current density is 1 C (1 C = 200 mA g -1 ) Cycle data. After 100 cycles, the material will be activated. As activation progresses, the discharge capacity gradually increases. The maximum discharge capacity is 106 mAh g -1 After 100 cycles, the specific capacity is 101 mAh g -1 , and its capacity retention rate is 95.3%. Figure 3 LB-2 synthesized in Example 2 was applied to sodium ion batteries. (a) First week charge and discharge data. The first week charge and discharge capacity was: 182 / 143 mAh g -1 (b)The current density is 1 C (1 C = 200 mA g -1 ) cycle data, which is cycled 100 times and its initial discharge capacity is 122.2 mAh g -1 After 100 cycles, the specific capacity is 111.9 mAh g-1, and the capacity retention rate is 91.6%.

[0046] Figure 4 LB-3 synthesized in Example 3 is applied to sodium ion batteries. (a) First week charge and discharge data. First week charge and discharge capacity: 320 / 258 mAh g -1 (b) Current density 1 C(1 C=200 mA g -1 ) cycle data. After 100 cycles, the initial discharge capacity is 234 mAh g -1 After 100 cycles, the specific capacity is 219 mAh g -1 , and its capacity retention rate is 93.8%.

[0047] Figure 5 LB-4 synthesized in Example 4 is applied to sodium ion batteries. (a) First week charge and discharge data. First week charge and discharge capacity: 267 / 205 mAh g -1 (b) Current density 1 C(1 C=200 mA g -1 ) Cycle data. After 100 cycles, the material will be activated. As activation progresses, the discharge capacity gradually increases. The maximum discharge capacity is 169 mAh g -1 After 100 cycles, the specific capacity is 149.1 mAh g -1 , and its capacity retention rate is 88.2%. Figure 6The LB-3 synthesized in Example 3 was assembled into a sodium ion battery and charged and discharged at high and low temperatures. At 60°C, its discharge capacity was 257.6 mAh g -1 , the charge and discharge curve at -40° is 175.4 mAh g -1 , indicating that the material still has good electrochemical properties under extreme conditions.

[0048] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization, characterized in that The following steps are involved: S1. Raw material mixing: weighing aniline monomer, surfactant and biomass enzyme respectively according to proportion and dissolving them in an organic solvent to obtain a raw material solution of aniline; S2, photopolymerization reaction: subjecting the polyaniline raw material solution of S1 to a polymerization reaction under ultraviolet light initiation irradiation to obtain a product solution; S3, separation of the first product: solid-liquid separation and drying of the product solution obtained in step S2 to obtain the first product; S4, nano-processing: the first product obtained in S3 is subjected to nano-processing to obtain a fully reduced polyaniline positive electrode material.

2. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: In step S1, the mass ratio of aniline to surfactant is 1-3.

3. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: In step S1, the mass ratio of aniline to biomass enzyme is 1-5.

4. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: In step S1, the mass ratio of aniline to the organic solvent is 3-20.

5. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: In step S2, the ultraviolet light is induced by irradiating with an ultraviolet lamp, and the ultraviolet light wavelength is 250-400 nm.

6. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: In step S3, the solid-liquid separation is carried out by filtration and / or centrifugal separation.

7. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: In step S3, the drying method is one or more of freeze drying, vacuum drying, and forced air drying, and the drying time is 5-20 hours.

8. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: In step S4, the nano-crushing method is one or more of mechanical grinding, impact grinding, ball milling, etching, and air flow milling.

9. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: In step S4, the control conditions for nano-milling are a ball milling speed of 200-400 rpm and a time of 3-10 h.

10. The method for preparing the fully reduced polyaniline cathode material by enzyme-catalyzed photopolymerization according to claim 1, characterized in that: The organic agent is one or more of toluene, n-hexane, dichloromethane, and N-methylpyrrolidone; the surfactant is one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polyoxyethylene fatty alcohol ether, fatty acid sorbitan, polyoxyethylene derivative alkyl alcohol amide, polyol monofatty acid ester, and essential oil emulsifier; the biomass enzyme is one or more of horseradish peroxidase (HRP), laccase, and soybean peroxidase.